Pengaruh Komitmen Organisasi Dan Work Engagement Terhadap Organizational Citizenship Behavior Karyawan PT. Bank Syariah Indonesia Kc Padang Imam Bonjol - Saputra, Andra Wibowo; Yulianti, Prima; Masruri, Masruri (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2025)
Bank Syariah Indonesia KC Padang Imam Bonjol is a company operating in the banking sector. To realize the creation of superior employee performance, banks need to foster and create employee behavior towards organizational citizenship behavior (OCB behavior). The aim of this research is to analyze the influence of organizational commitment and work engagement on organizational citizenship behavior of PT Bank Syariah Indonesia KC Padang Imam Bonjol employees. The type of research used in this research is a quantitative approach using the census method. This research refers to employees of PT Bank Syariah Indonesia KC Padang Imam Bonjol. The sample used in this research was 58 employees. The data collection method used was a questionnaire. The data analysis technique used is multiple linear regression analysis. The research results prove that organizational commitment has a positive and significant effect on organizational citizenship behavior, work engagement has a positive and significant effect on organizational citizenship behavior and organizational commitment and work engagement have a positive and significant effect on organizational citizenship behavior.